Teratogenic Effects of Diazepam - J Gordon Millichap (Pediatric Neurology Briefs, 1989)
Eight children exposed in utero to benzodiazepines, diazepam or oxazepam, and having dysmorphic characteristics resembling the fetal alcohol syndrome (FAS) are reported from the Department of Pediatrics, Gothenburg University, Sweden.